1963
DOI: 10.2466/pr0.1963.12.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Conditioned Emotional Response (CER) Following Lesions of the Amygdaloid Complex in Rats

Abstract: Formation of a conditioned emotional response (CER), using suppression of food-reinforced bar-pressing as an index, was studied in a group of rats with amygdaloid lesions ( N = 5) and in a sham-operate control group ( N = 5). In contrast to control animals, which typically suppressed in two to three sessions, none of the amygdaloid operates met criterion within the set limit of 15 sessions or showed signs of suppression. Increasing the intensity and duration of shock also proved ineffective in these animals. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…acquisition of a. conditioned emotiona1 response (CER) (Ke1licutt & Schwartzbaum, 1963). None of the 1esioned anima1s in this study showed any clear-cut evidence of suppression of a bar-pressing response for food reinforcement.…”
Section: Amygdalamentioning
confidence: 87%
“…acquisition of a. conditioned emotiona1 response (CER) (Ke1licutt & Schwartzbaum, 1963). None of the 1esioned anima1s in this study showed any clear-cut evidence of suppression of a bar-pressing response for food reinforcement.…”
Section: Amygdalamentioning
confidence: 87%
“…Similarly, the amygdala has been implicated in mediating conditioned emotional responses, including conditioned suppression. For instance, Kellicutt and Schwartzbaum (1963) trained rats with amygdala lesions to bar-press for food and then fear conditioned them. They found that rats with amygdala lesions took longer to suppress bar-pressing in response to the CS (Kellicutt and Schwartzbaum, 1963).…”
Section: Formation Of Aversive Memoriesmentioning
confidence: 99%
“…For instance, Kellicutt and Schwartzbaum (1963) trained rats with amygdala lesions to bar-press for food and then fear conditioned them. They found that rats with amygdala lesions took longer to suppress bar-pressing in response to the CS (Kellicutt and Schwartzbaum, 1963). Several years later, Goldstein (1965) reported that amygdala lesions resulted in deficits in the acquisition and retention of fear responses, as measured by the latency to jump out of a compartment in which a tone and shock were paired.…”
Section: Formation Of Aversive Memoriesmentioning
confidence: 99%
“…In the 1960s, it was shown that damage to the amygdala impairs conditioned suppression [(i.e. using the Estes–Skinner procedure) Kellicutt & Schwartzbaum (1963)] and by the early 1970s Robert and Caroline Blanchard had demonstrated an important role for both the amygdala and hippocampus in conditioned freezing behavior (Blanchard & Blanchard, 1972; Blanchard et al. , 1977).…”
mentioning
confidence: 99%